MAKNA TIJĀRAH DALAM AL-QUR’AN (PENDEKATAN TAFSIR SASTRAWI AMĪN AL-KHŪLĪ) - Nursaleha, Triade; Hakiki, Kiki Muhamad; Muttaqin, Ahmad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This research aims to examine the meaning of tijārah and the concept of trade in the Qur'an through a literary approach (al-manhaj al-adabī) developed by Amīn al-Khūlī. Using a descriptive qualitative method with a library research design, this study analyzes various primary and secondary sources, such as the Qur'an, books of tafsir, scientific books, journals, and related academic works. The data obtained is processed through the stages of reading, selecting, interpreting, and integrating the findings to produce a comprehensive understanding. The results show that the word tijārah in the Qur'an appears eight times, namely in Surah al-Baqarah/2:16 and 282, an-Nisā'/4:29, at-Tawbah/9:24, an-Nūr/24:37, Fāṭir/35:29, aṣ-Ṣaff/61:10, and al-Jumu'ah/62:11. Based on literary analysis, the term tijārah contains two main meanings: first, trading in the economic sense that involves potential profits and losses; second, spiritual commerce that describes the transactional relationship between man and God, which is metaphorical and always results in eternal benefits in the hereafter. Thus, this study confirms that the Qur'an not only contains the concept of trade in a worldly context, but also uses it as an ethical and spiritual symbol to build religious awareness in humans.